The Importance of Collaboration between Local Communities and Stakeholders in the Management of Volcano Ecotourism in Indonesia - Muryanti, Muryanti; Saputro, Agus; Ningtyas, Trimurti; Muryani, Tri; Yunia Sari, Qorir (Journal of Environmental Management and Tourism, 2026)
Collaboration is an important aspect in the development of ecotourism, considering that the provision of tourism experiences cannot be carried out by one stakeholder. Cooperation with interested stakeholders in the tourism sector is absolutely necessary. The objective of this paper examines the collaboration between local communities and stakeholders in managing ecotourism development in Volcanic Areas in Indonesia. Data collection was carried out by means of observation, and in-depth interviews were conducted with 18 stakeholders involved in implementing ecotourism projects in the cities of Yogyakarta and Kediri, as differing examples of major destinations Indonesia. To analyze it, this study used the theory of collaboration and community participation. Stakeholder mapping was divided into three key stakeholders groups (those who have legal authority in regulating activities), namely Tourism and Culture Office, Local Government at the village/ sub-district/ district level and Village-Owned Enterprises; Primary Stakeholders (those directly affected), namely private individuals/investors, communities, jeep drivers groups, travel agents, banking, community associations, tourism object associations, women farmers groups, mass media and the Office of Communication and Information; Secondary Stakeholders (as supporters of the course of tourism), namely Family Welfare Empowerment (Women's Organization), Karang Taruna, Sleman Museum Communication Forum, Universities, Social Services and Village Community Consultative Institutions. Collaboration is carried out in accordance with their respective roles in the management of the tourism sector, starting from the development of ideas/ideas, policies, managerial, research and publications, socialization processes, human resources for goods and services product business actors, capital, technology and the development of creativity as a form of creative economy. Collaboration between players in the ecotourismch sector needs to be much more extensive than it is currently to achieve the full potential of this industry.